A review on FRP-concrete hybrid sections for bridge applications. (15th April 2021) - Zou, Xingxing; Lin, Hongwei; Feng, Peng; Bao, Yi; Wang, Jingquan
Highlights: Reviewed the four manufacture techniques for FRP profiles. Reviewed six types of shear connections from the database of FRP-concrete shear connections. Reviewed three typical failure modes of FRP-concrete hybrid sections. Abstract: Development of durable, cost-effective bridges is a pressing research topic. Previous research and field applications have shown that fiber reinforced polymer (FRP)-concrete hybrid sections, including beams and decks, are attractive options for bridge superstructures. To date, there have been many experimental results, analytical approaches, and field applications scattered in the literature. This paper aims to review and evaluate FRP-concrete hybrid sections in the context of bridge engineering. Two databases of flexural tests and push-out tests of shear connections are developed, respectively. The paper is organized as follows: First, the characteristics of materials and structural configurations are introduced according to the database of flexural tests. Then, six typical types of shear connections from the database of push-out tests of FRP-concrete shear connections are compared. Next, three typical failure modes and deformation of FRP-concrete hybrid sections are separately analyzed with necessary design equations. Finally, case studies and perspective future development are discussed.